Effect of Intrauterine Administration of Proteolytic Enzymes on Fertility in Postpartum Crossbred Cows Affected with Subclinical Endometritis - Lakshmi Kotta, Radha; Allu, Teja; Konjeti, Anusha; Gaddam, Vani; Bojja, Chandana; Venkata Sai Narayana Prasad, Uppumaguluri (The Indian Journal of Animal Reproduction, 2026)
The present study was undertaken to evaluate and compare the effectiveness of intrauterine administration of proteo lytic enzymes with conventional antibiotic therapy and an untreated control, focusing on their effects on cervical mucus characteristics, evidence of PMN cell percentages, recovery and subsequent fertility in crossbred cows afflicted with subclinical endometritis. Group I received intrauterine proteolytic enzyme infusion containing trypsin, chymotrypsin, and papain; Group II received systemic antibiotic ceftiofur sodium intramuscularly for three days; and Group III served as the control group. 87.50% of animals in both Group I and II showed clear thin mucus while Group III animals showed no improvement. The mean spinnbarkeit values after treatment increased significantly in Group I and II. The mean pH values of cervical mucus in Group I and II was 7.12 ± 0.10, whereas Group III retained an alkaline pH (8.00 ± 0.10). The mean percentage of PMN cells recorded significant reductions Group I and II, while Group III remained unchanged after treatment. The first service conception rate among clinically recovered animals was 57.14% in Group I, 42.85% in Group II and 0% in Group III. Though conception rates were comparable between Group I and II, the enzyme group showed slightly higher fertility restoration. The results of the present study suggest that intrauterine administration of proteolytic enzymes improves cervical mucus quality, reduces uterine inflammation, and enhances fertility outcomes in cows with subclinical endometritis.
Keywords: Crossbred cows; Fertility; Proteolytic enzymes; Subclinical endometritis